Pazopanib for metastatic soft-tissue sarcoma (PALETTE): a randomised, double-blind, placebo-controlled phase 3 trial - Graaf, Wilhelmina Tita Alide van der; Blay, Jean-Yves; Hohenberger, Peter (The lancet, 2012)
Summary - Background - Pazopanib, a multitargeted tyrosine kinase inhibitor, has single-agent activity in patients with advanced non-adipocytic soft-tissue sarcoma. We investigated the effect of pazopanib on progression-free survival in patients with metastatic non-adipocytic soft-tissue sarcoma after failure of standard chemotherapy. - Methods - This phase 3 study was done in 72 institutions, across 13 countries. Patients with angiogenesis inhibitor-naive, metastatic soft-tissue sarcoma, progressing despite previous standard chemotherapy, were randomly assigned by an interactive voice randomisation system in a 2:1 ratio in permuted blocks (with block sizes of six) to receive either pazopanib 800 mg once daily or placebo, with no subsequent cross-over. Patients, investigators who gave the treatment, those assessing outcomes, and those who did the analysis were masked to the allocation. The primary endpoint was progression-free survival. Efficacy analysis was by intention to treat. The trial is registered with ClinicalTrials.gov, number NCT00753688. - Findings - 372 patients were registered and 369 were randomly assigned to receive pazopanib (n=246) or placebo (n=123). Median progression-free survival was 4·6 months (95% CI 3·7-4·8) for pazopanib compared with 1·6 months (0·9-1·8) for placebo (hazard ratio [HR] 0·31, 95% CI 0·24-0·40; p<0·0001). Overall survival was 12·5 months (10·6-14·8) with pazopanib versus 10·7 months (8·7-12·8) with placebo (HR 0·86, 0·67-1·11; p=0·25). The most common adverse events were fatigue (60 in the placebo group [49%] vs 155 in the pazopanib group [65%]), diarrhoea (20 [16%] vs 138 [58%]), nausea (34 [28%] vs 129 [54%]), weight loss (25 [20%] vs 115 [48%]), and hypertension (8 [7%] vs 99 [41%]). The median relative dose intensity was 100% for placebo and 96% for pazopanib. - Interpretation - Pazopanib is a new treatment option for patients with metastatic non-adipocytic soft-tissue sarcoma after previous chemotherapy. - Funding - GlaxoSmithKline.